An economic analysis on internet regulation in China and proposals to policy and law makers. (2016) - Liao, Zhixiong
China has enacted and enforced 70-more internet-regulation related pieces of laws and regulations, and the so-called 'real name registration' scheme is to be implemented by the end of June 2014. To date, China has established comprehensive legal framework and sophisticated multi-level law enforcement mechanism to regulate the contents on internet. This paper undertakes an economic analysis of the internet contents regulation in China, aiming to find out a possible answer to the question of whether the current regulation regime in China on internet contents is cost-effective, feasible and maintainable and hence justifiable and desirable, taking into account the short-term and long-term welfare of the community. Based on the analysis, this paper makes submissions to policy and law makers accordingly.